Answer:
f(x) = - (x - 5)² - 5
Step-by-step explanation:
The vertex form of the quadratic function is:
![\begin{gathered} f\mleft(x\mright)=a\mleft(x-h\mright)^2+k \\ \text{where (h,k) is the vertex} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/btj1omzkm8em2tphpnylvgtc9dfdua3qzh.png)
Given that it has a vertex at (5, -5),
(h,k)=(5,-5)
![\begin{gathered} f(x)=a(x-5)^2+(-5) \\ f(x)=a(x-5)^2-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4jbz8hs0k8v38gbk0ykqgt9lvxmn7oww0a.png)
Since it passes through the point (7,-9)
When x=7, f(x)=-9
![\begin{gathered} -9=a(7-5)^2-5 \\ -9=a*2^2-5 \\ -9+5=4a \\ -4=4a \\ a=(-4)/(4)=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/naovqyk1obt77hlxelms1xw7a8m5ibav14.png)
Therefore, the function is:
f(x) = - (x - 5)² - 5